2008
DOI: 10.1002/pros.20856
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of 177Lu‐CHX‐A″‐DTPA‐hu3S193 radioimmunotherapy in prostate cancer is enhanced by EGFR inhibition or docetaxel chemotherapy

Abstract: BACKGROUND. This study investigated the biodistribution and therapeutic efficacy of 177 Lu) radiolabeled anti-Lewis Y monoclonal antibody hu3S193 radioimmunotherapy (RIT) in mice bearing prostate cancer xenografts. The ability of epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor AG1478 and docetaxel chemotherapy to enhance the efficacy of RIT was also assessed in vivo. METHODS. The in vitro cytotoxicity of 177 Lu labeled hu3S193 on Le y positive DU145 prostate cancer cells was assessed using p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 44 publications
(57 reference statements)
5
27
0
Order By: Relevance
“…As an example, the maximum follow-up time was respectively 77 and 102 days in two studies performed with antibodies labeled with lutetium-177 [6,7]. However, in one study performed with a 177 Lu-labeled anti-Lewis Y antibody the maximum follow-up time was 150 days after injection of an activity of 12.95 MBq, comparable to that of the present study, and no oncogenic effect was observed [8]. Furthermore, a lot of preclinical studies have been carried out with antibodies labeled with iodine-131, which has a half-life longer than that of lutetium-177, and oncogenic effects have never been reported.…”
supporting
confidence: 76%
“…As an example, the maximum follow-up time was respectively 77 and 102 days in two studies performed with antibodies labeled with lutetium-177 [6,7]. However, in one study performed with a 177 Lu-labeled anti-Lewis Y antibody the maximum follow-up time was 150 days after injection of an activity of 12.95 MBq, comparable to that of the present study, and no oncogenic effect was observed [8]. Furthermore, a lot of preclinical studies have been carried out with antibodies labeled with iodine-131, which has a half-life longer than that of lutetium-177, and oncogenic effects have never been reported.…”
supporting
confidence: 76%
“…Furthermore, a plethora of preclinical data have emerged indicating that treatment with various protein kinase inhibitors confers radiosensitivity on prostate cancer models, including those that target Akt, sphingosine kinase, aurora kinase A and B, and Wee1 (37)(38)(39)(40)(41). Most of these studies used external-beam radiation; however, 1 group reported additive effects when a 177 Lu-labeled anti-Lewis Y monoclonal antibody was combined with an epidermal growth factor receptor kinase inhibitor in an in vivo prostate cancer model (42).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of radioimmunotherapy with chemotherapy to induce enhanced antitumor effects has been extensively explored in preclinical models (23)(24)(25)(26)(27)(28) and in a small number of phase I/II studies in patients with advanced solid tumors, with a suggestion of antitumor activity in some (29)(30)(31)(32)(33)(34). The aim of this approach is to use chemotherapy as a radiosensitizer, so that cancer cell cycle is arrested in the radiosensitive G(2)/M phase and efficacy is improved.…”
Section: Discussionmentioning
confidence: 99%